2021
DOI: 10.3390/min11080863
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Bio-Coal Applications in the Blast Furnace Process—Opportunities and Limitations

Abstract: Metal production, and especially iron ore-based steel production, is characterized by high fossil CO2 emissions due of the use of coal and coke in the blast furnace. Steel companies around the world are striving to reduce the CO2 emissions in different ways, e.g., by use of hydrogen in the blast furnace or by production of iron via direct reduction. To partially replace fossil coal and coke with climate neutral bio-coal products that are adapted for use in the metal industry, e.g., at the blast furnace, is a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…In general, for good-quality coke, the CSR index must be high, whereas the CRI is low [53]. In this work, up to 15 wt.% of the coconut shells, CSR index (55.1%), and CRI index (29.8%) remained at workable-level biocoke for blast-furnace applications, which is CSR 74-50 and CRI 19-30 [2,31,39,54].…”
Section: Csr and Cri Testsmentioning
confidence: 68%
“…In general, for good-quality coke, the CSR index must be high, whereas the CRI is low [53]. In this work, up to 15 wt.% of the coconut shells, CSR index (55.1%), and CRI index (29.8%) remained at workable-level biocoke for blast-furnace applications, which is CSR 74-50 and CRI 19-30 [2,31,39,54].…”
Section: Csr and Cri Testsmentioning
confidence: 68%
“… 134 However, fuel injection via the tuyeres is considered by many as the easiest way to mitigate CO 2 emissions via the use of bio-coal as it does not significantly affect the BF performance. 135 In fact, it was reported that the complete substitution of coal by bio-coal for fuel injection had equal or better combustion performance than its fossil counterpart. 136 It was estimated that a 33% reduction in CO 2 emission could be obtained using 100% charcoal for fuel injection.…”
Section: Greener Reactants and Recycled Feeds In Pyrometallurgymentioning
confidence: 99%
“… 136 It was estimated that a 33% reduction in CO 2 emission could be obtained using 100% charcoal for fuel injection. 135 In the work of Okvist and Lundgren, 135 it was found that the substitution of 5% biocoal in briquettes and 2–5% in coke had moderate beneficial impacts on the BF CO 2 emissions while not impairing too much the behaviour of the reactor. 135 In another study, the successful incorporation of briquettes containing 1.8 wt% torrefied saw dust in a BF for several weeks was demonstrated.…”
Section: Greener Reactants and Recycled Feeds In Pyrometallurgymentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of replacing part of the fossil coal with bio-coal is that the biomass regeneration time is comparatively short [4] and the effects on global warming can be reduced as the carbon cycle is closed [5]. It has been reported that with the partial replacement of coking coals with 5-10% of bio-coal, the fossil CO 2 emissions at the BF can be lowered by ~4-8% [6]. Using bio-coke (bio-coal-containing coke) in the BF has the potential to lower the thermal reserve zone temperature (TRZT) of the BF, as the gasification reaction (reaction of carbon in coke with CO 2 ) can proceed at a lower temperature in the more reactive bio-coke.…”
Section: Introductionmentioning
confidence: 99%